Design of a Meeting Attendance System Based on Dynamic QR Code with Universally Unique Identifier (UUID v4) - Kholifah Dwi Annurrahma; Sayekti Harist Suryawan; Abdul Rahim (Jurnal Riset Informatika, 2025)
Manual attendance systems are still widely used in various institutions, including the Quality Assurance Agency of Muhammadiyah University of East Kalimantan (LJM UMKT), despite their limitations such as vulnerability to data manipulation, slow recapitulation, and paper dependency. This study aims to design and implement a digital meeting attendance system using dynamic QR Codes generated with UUID version 4, combined with GPS-based location validation. The system was developed using the prototyping method through stages of requirements analysis, UML-based system modeling, technical design with Flask and MySQL, prototype development, testing, and evaluation. System testing was carried out using the black-box method to verify functional performance, while evaluation was conducted using the Technology Acceptance Model (TAM), focusing on three constructs: Perceived Usefulness (PU), Perceived Ease of Use (PEOU), and Behavioral Intention to Use (BI). The testing results demonstrate that the system runs stably and effectively validates attendance based on time and location. Evaluation with 16 respondents indicated high user acceptance, with PU at 94.6%, PEOU at 88%, and BI at 96%. These findings suggest that the QR Code-based attendance system with UUID v4 significantly improves efficiency, accuracy, and security in recording meeting attendance and has strong potential for broader implementation in educational institutions and organizations.